Natural cellulose fibers derived from Dracaena angolensis (Welw. ex Carrière) Byng & Christenh. demonstrate potential as a non-absorbable surgical suture biomaterial - Piyaporn Kampeerapappun; Scarlett Desclaux; Kasem Rattanapinyopituk; Tanyalak Srisuk; Ruedee Hemstapat (Scientific Reports)
Abstract Sutures from natural and synthetic materials are utilized to close wounds, stop bleeding, reduce pain and infection, repair cutaneous wounds, minimize scarring, and promote optimal wound healing. We used mechanical and chemical methods to extract cellulose fibers from cylindrical snake grass (Dracaena angolensis) (Welw. ex Carrière) Byng & Christenh. Following the extraction process, the fibers increased in cellulose and water content, while hemicellulose and lignin decreased. The extracted fibers exhibited good mechanical properties, with weight losses of 7.4% in deionized water (DI) and 13.7% in phosphate-buffered saline (PBS). In comparison, the commercial braided silk sutures (Mersilk braided silk non-absorbable suture) used as a control showed no weight loss. However, the morphology of the fibers remained consistent throughout the 35-day immersion period in either DI or PBS. In an in vivo biocompatibility test, a semi-quantitative analysis of host tissue reactions indicated no significant difference (p > 0.05) between the two suturing materials across all criteria, confirming the comparable biocompatibility of cylindrical snake grass fibers to that of commercial silk sutures. These findings demonstrate the promising potential of natural cellulose fibers derived from cylindrical snake grass as an alternative source of a non-absorbable surgical suture biomaterial, attributed to their outstanding mechanical properties and biocompatibility.